Fish oil LC-PUFAs do not affect blood coagulation parameters and bleeding manifestations: Analysis of 8 clinical studies with selected patient groups on omega-3-enriched medical nutrition - Jeansen, Stephanie; Witkamp, Renger F.; Garthoff, Jossie A.; van Helvoort, Ardy; Calder, Philip C. (Clinical nutrition (Edinburgh, Scotland), 2018)
The increased consumption of fish oil enriched-products exposes a wide diversity of people, including elderly and those with impaired health to relatively high amounts of n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFAs). There is an ongoing debate around the possible adverse effects of n-3 LC-PUFAs on bleeding risk, particularly relevant in people with a medical history of cardiovascular events or using antithrombotic drugs. This analysis of 8 clinical intervention studies conducted with enteral medical nutrition products containing fish oil as a source of n-3 LC-PUFAs addresses the occurrence of bleeding-related adverse events and effects on key coagulation parameters (Prothrombin Time [PT], (activated) and Partial Thromboplastin Time [(a)PTT]). In all the patients considered (over 600 subjects treated with the active product in total), with moderate to severe disease, with or without concomitant use of antithrombotic agents, at home or in an Intensive Care Unit (ICU), no evidence of increased risk of bleeding with use of n-3 LC-PUFAs was observed. Furthermore there were no statistically significant changes from baseline in measured coagulation parameters. These findings further support the safe consumption of n-3 LC-PUFAs, even at short-term doses up to 10 g/day of eicosapentaenoic acid + docosahexaenoic acid (EPA + DHA) or consumed for up to 52 weeks above 1.5 g/day, in selected vulnerable and sensitive populations such as subjects with gastrointestinal cancer or patients in an ICU. We found no evidence to support any concern raised with regards to the application of n-3 LC-PUFAs and the potentially increased risk for the occurrence of adverse bleeding manifestations in these selected patient populations consuming fish oil enriched medical nutrition.